Servicios ecosistémicos y cantidad de carbono acumulado en la biomasa de plantaciones de Ochroma pyramidale (Cav. Ex Lam.) Urb. (Balsa) de los cantones buena fe y quevedo, provincia de los ríos - Parra Parra, Juleysi Mariana (2024)
Ecosystem services, understood as the tangible and intangible benefits that ecosystems provide to humanity, one of the most important services provided by forest ecosystems is the capture and storage of carbon. The aim was to determine the ecosystem services and amount of carbon accumulated in the biomass of Ochroma pyramidale (Cav. Ex Lam.) Urb. (Balsa) plantations. The methodology used in this study was conducted in five-year-old O. pyramidale plantations. It was decided to use square plots of 100 x 100 meters (10,000 m²) as sampling units. From each of these plots, subplots of 20 x 25 meters (500 m²) were taken, placed at the corners of the plots, leaving an adjacent effect space, carried out in the Buena Fe and Quevedo cantons of Los Ríos province. The results revealed that concerning dasometric variables in O. pyramidale, the Quevedo location exhibited the highest average values in Diameter at Breast Height (DBH), with measurements of 25.37 cm and 24.80 cm. The accumulated carbon quantity was greater for the 0-20 cm depth range with percentage values of 2.7 and 1.6. The carbon in the aboveground biomass recorded highly significant results with a value of 3.95 per replication, 5.00 at the location, 6.3 at the farms, and 8.98 in the interaction between location and farms. The statistics of the results obtained in system carbon with 40.5 Tm-1, necromass carbon with 9.8 Tm-1, biomass carbon with 70.6 Tm-1, and total biomass with 5.5 Tm-1 in location 1 (Buena Fe). In location 2 (Quevedo), values in system carbon were 38.8 Tm-1, necromass carbon 9.8 Tm-1, biomass carbon 71.3 Tm-1, and total biomass 5.4 Tm-1. These results provide a quantitative insight into the carbon content in different components of the forest ecosystem in the two analyzed locations.